2020
DOI: 10.1017/ipm.2020.46
|View full text |Cite
|
Sign up to set email alerts
|

Can we expect an increased suicide rate due to Covid-19?

Abstract: Human disasters come in all shapes and sizes including wars, terrorist violence, natural events, economic recessions and depressions as well as infection. As a species more fragile than we often allow, humans would be expected to adversely react to these types of disasters in terms of mental ill health and possibly suicidal behaviour leading to increased demands on the Mental Health services. This narrative historical paper examines relevant studies into how previous disasters affected mental health and suicid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 21 publications
(18 reference statements)
1
44
0
5
Order By: Relevance
“…Most studies have discussed suicidal risk following acute traumatic events like natural calamities. The pandemic being a chronic phenomenon with uncertain and sustained biopsychosocial effects for months to come is different from them, and thus that research cannot be translated to relevance for the current crisis ( Devitt, 2020 ). Suicide rates had increased during the classic ‘pestilences’ of the bubonic plague ( Benedictow and Benedictow, 2004 ).…”
Section: Covid-19 and Suicide: The Problem Statementmentioning
confidence: 99%
“…Most studies have discussed suicidal risk following acute traumatic events like natural calamities. The pandemic being a chronic phenomenon with uncertain and sustained biopsychosocial effects for months to come is different from them, and thus that research cannot be translated to relevance for the current crisis ( Devitt, 2020 ). Suicide rates had increased during the classic ‘pestilences’ of the bubonic plague ( Benedictow and Benedictow, 2004 ).…”
Section: Covid-19 and Suicide: The Problem Statementmentioning
confidence: 99%
“…Other studies about SARS-related mental health issues were conducted in the doctors 14 , nurses [14][15][16] , and overall hospital workers 17 . In addition, even though several studies have warned of a potential rise of suicides in the COVID-19 18,19 , there were limited reports on the topic of post-SARS suicides 20,21 . Therefore, a nationwide, populationbased, long-term study on the topic for psychiatric disorders and suicides for the patients with SARS is yet to be conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Our concern is the future growth of suicide rates, especially in Post-COVID-19 times. Psychological distress, psychiatric disorders, and suicide rates could increase after a crisis such as natural disasters or economic recessions (10,11). Alongside other studies, which did not show increases in the suicide rate during the COVID-19 pandemic (12), registered data of the Ministry of health indicated that during the first six months since the beginning of COVID-19 in Iran, the rate of suicide and suicide attempts has not increased from the corresponding date of last year.…”
mentioning
confidence: 90%